Initial Consonant Deletion in Bilingual Spanish-English Speaking Children with Speech Sound Disorders - Fabiano-Smith, Leah (Clin Linguist Phon, 2017)
The purpose of this study was to utilize a theoretical model of bilingual speech sound production as a framework for analyzing the speech of bilingual children with speech sound disorders. In order to distinguish speech difference from speech disorder, we examined between-language interaction on initial consonant deletion, an error pattern found cross-linguistically in the speech of children with speech sound disorders. Thirteen monolingual English-speaking and bilingual Spanish and English-speaking preschoolers with speech sound disorders were audio-recorded during a single word picture-naming task and their recordings were phonetically transcribed. Initial consonant deletion errors were examined both quantitatively and qualitatively. An analysis of cross-linguistic effects and an analysis of phonemic complexity were performed. Monolingual English-speaking children exhibited initial consonant deletion at a significantly lower rate than bilingual children in their Spanish productions; however, no other quantitative differences were found across groups or languages. Qualitative differences yielded between-language interaction in the error patterns of bilingual children. Phonemic complexity appeared to play a role in initial consonant deletion. Evidence from the speech of bilingual children with speech sound disorders supports analyzing bilingual speech using a cross-linguistic framework. Both theoretical and clinical implications are discussed.